Menjejak semangat ‘Kawi’: Langkawi sebagai Geopark - Ong , Puay Liu; Nur Hafizah Yusoff,; Sharina Abdul Halim, (Universiti Kebangsaan Malaysia, 2010)
In June 2007, Langkawi Islands received the status “Global Geopark” from GGN UNESCO, thus making Langkawi the first global geopark in Malaysia and Southeast Asia, and the 52nd in the world. Geopark embodies the philosophy of protection, education and sustainable development of a specific geoheritage site characterised by unique and rare geological features. However, a distinctive feature that upholds the status of a geological site as a geopark is‘usage’ – the existence of a close connectivity between geological resources and the way of life of the human community living in its vicinity. Hence, a geopark recognises the interdependent and integrated relationship between the natural heritage and human heritage. The aim of a geopark is to produce a community of people who are knowledgeable about the natural heritage, and the close relationship between these natural resources and the life of the people; who internalise the importance of protecting both natural and socio-cultural heritages; who carry out activities that are sustainable and heritage-friendly. The writers view this aim of producing people who know, internalise and actualise the concept of geopark as embodying the “kawi spirit” – a spirit that is moved by the principles of protection and conservation of natural and sociocultural heritage. Has this ‘kawi spirit’ emerged in the hearts of the local community and those promoting Langkawi to tourists? More specifically, have they understood the geopark concept? Without such conceptual understanding, the local community and tour operators will not be able to visualise the aim of a geopark and appropriate actions that need to be taken. This situation limits the understanding of their role as ‘guardians’ and ‘stewards’ of Langkawi Geopark. These questions serve as guiding principles for this article in an effort to track the ‘kawi’ spirit among the local community and tour operators at Langkawi